Rising powers and peacebuilding : breaking the mold? - Call, Charles T. ; Coning, Cedric de (Palgrave Macmillan, 2020)
Contents: Why examine rising powers' role in peacebuilding? Cedric de Coning and Charles T. Call -- A "Brazilian way"? : Brazil's approach to peacebuilding Adriana Erthal Abdenur and Charles T. Call -- Offering support and sharing experiences : Indonesia's approach to peacebuilding Lina A. Alexandra -- Peacebuilding through development partnership : an Indian perspective P.K. Singh -- Breaking with convention : Turkey's new approach to peacebuilding Onur Sazak and Auveen Elizabeth Woods -- South African peacebuilding approaches : evolution and lessons Charles Nyuykonge and Siphamandla Zondi -- Rising powers and peacebuilding: India's role in Afghanistan Shakti Sinha -- Thinking outside the compound : Turkey's approach to peacebuilding in Somalia Onur Sazak and Auveen Elizabeth Woods -- New actors and innovative approaches to peacebuilding : the case of Myanmar Lina A. Alexandra and Marc Lanteigne -- Are rising powers breaking the peacebuilding mold? Charles T. Call and Cedric de Coning.